IMPLEMENTATION OF ENGLISH LEARNING USING SPEECH RECOGNITION TECHNOLOGY (Case study at SMA Negeri 1 Serang Panjang, Subang Regency) - Ida Maulida (Jurnal Education and Development, 2021)
English is a language of communication that plays a very important role in connecting between countries. In communicating can convey orally or in writing so that there is no misunderstanding in providing information. People from various countries are encouraged to learn English to add insight in keeping up with the times. In Indonesia itself, English is a foreign language that must be learned, from elementary school to university level, to introduce English to students so that it can be applied in different and fun methods, the design of Speech Recognition applications based on windows 10 and Android it is hoped that it can accelerate the application of English much more interactively and increase students' interest. Speech Recognition itself (speech recognition) is the development of techniques and systems that allow computers to receive input in the form of spoken words. This technology allows the device to recognize and understand spoken words by digitizing the words and matching the digital signal to a specific pattern stored in the device. Spoken words are converted into digital signals by converting sound waves into a series of numbers which are then matched with a special code to identify the words.